2018
DOI: 10.1128/jvi.02006-17
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Epitope-Specific Mechanisms of Neutralization of Influenza Virus by Intact IgG and Fab Fragments

Abstract: The neutralizing antibody (nAb) response against the influenza virus's hemagglutinin (HA) fusion glycoprotein is important for preventing viral infection, but we lack a comprehensive understanding of the mechanisms by which these antibodies act. Here we investigated the effect of nAb binding and the role of IgG bivalency on inhibition of HA function for nAbs targeting distinct HA epitopes. HC19 targets the receptor-binding pocket at HA's distal end, while FI6v3 binds primarily to the HA2 fusion subunit towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
4
18
0
Order By: Relevance
“…We unequivocally demonstrate that anti-stem Ab have sufficient access to HA on intact virions to inhibit NA activity, extending cryoelectron microscopy-based observations that Abs can access HA stem on intact virions (Harris et al, 2013;Wasilewski et al, 2012;Williams et al, 2017). Examination of the Ab NAI titration curves (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…We unequivocally demonstrate that anti-stem Ab have sufficient access to HA on intact virions to inhibit NA activity, extending cryoelectron microscopy-based observations that Abs can access HA stem on intact virions (Harris et al, 2013;Wasilewski et al, 2012;Williams et al, 2017). Examination of the Ab NAI titration curves (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…We first analyzed the theoretical binding pattern of ZK2B10 to the DIII domains on a single Zika virion. We found that the distance between the C-terminal CH1 residue (K235) of fitted FabZK2B10 was <86 Å , which would allow bivalent binding (Edeling et al, 2014;Fibriansah et al, 2015;Harris et al, 1997;Williams et al, 2017). As shown in Figure 5D, bivalent binding could occur between the adjacent DIIIs near the 5-fold axes (between 37 and 76 Å ), but not the 3-fold or 2-fold axes (114 Å ).…”
Section: Comparable Binding and Neutralization Between Igg And Fab Fomentioning
confidence: 89%
“…Expression of HA2 in the absence of HA1 yields HA2 in its post-fusion conformation [27][28][29]77]. Furthermore, preventing HA1 s dissociation Viruses 2020, 12, 413 6 of 21 either through the introduction of interprotomer disulfide bonds or antibody binding renders HA non-fusogenic, but these restraints still enable the HA2 fusion peptide to release and interact with target membranes [28,29,[77][78][79].…”
Section: Despite Their Common Architectures Activation Mechanisms Anmentioning
confidence: 99%